Leptospira infection and carrier survey on rats from wet market areas in Kuala Lumpur, Malaysia - Noh, Mohamed Asyraf; Masri, Siti Norbaya; Zulkapli, Azlina; Mohd Ali, Mohammad Ridhuan; Amran, Fairuz (Medknow Publications, 2024)
Background & objectives: Leptospirosis is an important zoonotic infection that has caused significant mortality and morbidity worldwide. This disease is endemic in Malaysia and as a developing tropical country, leptospirosis is concerning as it threatens Malaysian public health and the country’s economic sectors. However, there is limited information on leptospirosis in Malaysia, especially regarding leptospiral seroepidemiology among carriers in Malaysia. Therefore, more epidemiological information on the source of the disease and reservoir are needed for better disease control and source intervention. The objectives of this study are to gather information on Leptospira infection and the carrier status of rats captured from selected wet markets of Kuala Lumpur metropolitan city in Malaysia. Methods: Live rat trappings were performed in four major wet markets in Kuala Lumpur, namely, Pudu, Chow Kit, Datuk Keramat, and Petaling Street. Animal samplings were performed for 12 months in 2017, where blood and kidney samples were collected and tested for anti-leptospiral antibodies via Microscopic Agglutination Test (MAT) and pathogenic Leptospira screening via Polymerase Chain Reaction (PCR) amplification of flaB gene. Results: MAT showed that 34.7% (n = 50/144) of the captured rats were positive for anti-leptospiral antibody of which the most prominent serovar was Malaya followed by a local strain, IMR LEP 175. In parallel, 50 rats were also positive for pathogenic Leptospira DNA. Interpretation & conclusion: This study showed that there are persistent Leptospira infections among rats in Kuala Lumpur wet markets and these rats are important reservoir hosts for the bacteria.